Increasing Student’s Learning Activity on Trigonometry Material through a Contextual-Based Group Investigation Learning Model - Iswadi, Iswadi (PPSDP International Journal of Education, 2024)
Mathematics is the least preferred and most difficult subject for most students, especially when it comes to trigonometry. This is reflected in student learning outcomes and students’ daily test results, which are always lower than other majors, and a maximum of 40% of students graduate. One of the causes is a lack of interest in teaching and learning in the classroom. Therefore, it is necessary to carry out learning activities with a learning model that is expected to make learning conditions or environments more comfortable for students. The process consists of two cycles using the group investigation learning model. At the end of the study, the following results were obtained: In Cycle I, the average student achievement was 31,6 percent; in Cycle II, it rose to 70,3 percent. Mastery of subjects also increased, which increased the average student achievement from 63,5% in cycle I to 64,9% in cycle II.